Cluster forming based on spatial information using HMAC in WSN - Aso Ahmed Majeed (Tikrit Journal of Pure Science)
The wireless sensor can be considered as one of the most major technologies through using it in different application such as environmental applications, military applications, commercial applications, health applications and agriculture applications. Due to the sensor networks may be deployed in open area (uncontrolled area), especially in military applications. In such situations, the nodes are vulnerable to be captured. Moreover, data/control packets may be intercepted and/or modified due to the transmission nature.